Methyl-aminolevulinic acid photodynamic therapy for actinic keratoses: a useful treatment or a risk factor? A retrospective study. (April 2015) - Bardazzi, F.; Loi, C.; Magnano, M.; Burtica, E. C.; Giordano, F.; Patrizi, A.
Abstract Introduction: Photodynamic therapy (PDT) is a non-invasive treatment, used for superficial non-melanoma skin cancer (NMSC) and actinic keratoses (AKs). Although PDT is considered a safe treatment, some authors report that PDT may have carcinogenic risks. We undertook this retrospective study to determine if there is a real risk of carcinogenicity for patients treated with MAL-PDT for AK and which risk factors may increase the rate of the malignant transformation. Methods: We reviewed the records of patients treated with PDT for one or more AKs at the Sant'Orsola-Malpighi Hospital from January 2010 to December 2012. We also considered if patients had one or more risk factors for NMSC. Results: Three hundred fifty-seven patients were treated with PDT for AKs, among them 17 patients developed a squamous cell carcinoma (SCC) in the site of a lesion previously treated with PDT. Comparing these two groups, the group which developed the SCC presented more risk factors for NMSC. Conclusion: PDT is certainly a good method to treat AKs, but it is important also to consider all its side effects. Among them, the carcinogenetic risk is still underestimated. We suggest that patients with multiple risk factors for NMSC treated with PDT should undergo more frequent follow-ups, in order to prevent malignant progression.